Estrogen Deficiency Impairs Osseointegration in Hypertensive Rats Even Treated with Alendronate Coated on the Implant Surface - Mulinari-Santos, Gabriel [UNESP] (2023)
Hypertension and estrogen deficiency can affect bone metabolism and therefore increase the risk of osseointegration. Antihypertensive drugs such as losartan not only control blood pressure but also enhance bone healing. In addition, alendronate sodium is widely used to treat postmenopausal osteoporosis. Hence, we evaluated the effect of systemic antihypertensive and local alendronate coted on implants on osseointegration under hypertensive and estrogen-deficiency conditions. A total of 64 spontaneously hypertensive rats (SHRs) treated with losartan were randomly divided according to the estrogen-deficiency induction by ovariectomy (OVX) or not (SHAM), and whether the implant surface was coated with sodium alendronate (ALE) or not, resulting in four groups: SHR SHAM, SHR SHAM ALE, SHR OVX, and SHR OVX ALE. The removal torque, microcomputed tomography, and epifluorescence microscopy were the adopted analyses. The hypertensive and estrogen-deficiency animals presented a lower removal torque even when treated with alendronate on implant surface. The microcomputed tomography revealed a higher bone volume and bone-to-implant contact in the SHRs than the SHR OVX rats. Epifluorescence showed a decreased mineral apposition ratio in the SHR OVX ALE group. The data presented indicate that estrogen deficiency impairs osseointegration in hypertensive rats; in addition, alendronate coated on the implant surface does not fully reverse this impaired condition caused by estrogen deficiency.